SCREENING OF INDIAN HERBS FOR HAEMOSTATIC ACTIVITY - Jadhav, Shital Tanaji (Journal of Drug Delivery and Therapeutics, 2013)
India is one of the important widespread geographic locationsÂ on mega biodiversity areas on earth. The rich cultural heritage of India is also associated with the use of available ethno medicinalÂ flora and fauna since ages. To raise this traditional knowledge to global level and to serve the mankind using the same, Â a systematic modern approach has been adopted here to ascertain the rational use of traditionally applied Indian herbs for the purpose of healing wounds and controlling haemorrhage from cuts and bruises. In vitro clotting time of blood in presence and Â absence Â of various plant extracts was used as a guide to study haemostatic activityof the herbs under study. Of the ten plants evaluated, aqueous extracts of Quercus pubescens, Thevetia peruviana proved to haveÂ significantÂ haemostatic activity at P<0.05 as judgedÂ by Chi Square goodness of fit test, whereas alcoholic extracts of Zingiber officinale, Zanthoxylum rhetsa and petroleum ether extracts of Psidum guajava, Terminalia chebula, Zanthoxylum rhetsa confirmed the same results.